Audit review and audit outcome of tax auditors in Thailand: moderating effects of professional skepticism and audit experience. (4th November 2022) - Phornlaphatrachakorn, Kornchai; Kalasindhu, Khajit Na
This study aims at examining the relationships between audit review and audit outcome of tax auditors in Thailand through moderating effects of professional skepticism and audit experience. In this study, 195 tax auditors in Thailand are the samples of the study. Both structural equation modelling and multiple regression analysis are applied to test the research relationships. The results indicate that audit review positively affects audit efficiency and audit effectiveness, but it has no effect on audit quality and audit outcome. Both audit efficiency and audit effectiveness have a positive influence on audit quality and audit outcome, but audit quality does not relate to audit outcome. Also, professional skepticism is a moderator of the audit review-audit efficiency relationships and audit experience has a moderating effect on the audit efficiency-audit outcome relationships and the audit effectiveness-audit outcome relationships. Thus, audit review plays an important role in directly determining both audit efficiency and audit effectiveness and in indirectly explaining audit outcome. Accordingly, auditors should pay attention to studying, understanding and learning characteristics, qualifications and applications of audit review and utilise it as an excellent audit practice to increase audit efficiency, audit effectiveness, and audit outcome.